The adoption of children from out-of-home care: The understandings of key decision makers in Victoria, Australia. (October 2017) - Butlinski, Anna; Rowe, Heather; Goddard, Christopher; Freezer, Nicholas
Abstract: Adoption is one of a range of options that can provide children in out-of-home care with permanency when they are unable to be reunified with their birth parents. This paper reports on how the adoption of children from out-of-home care is understood by professionals involved in making decisions about the permanent placement of children in out-of-home care in Victoria, Australia, where adoption is rarely used. Data were collected through a single, face-to-face semi-structured interview with 21 professionals; eight child welfare specialists, eight adoption and permanent care specialists and five judicial officers. The adoption of children from out-of-home care was primarily understood as a child-centered practice that can afford children stability and a sense of belonging. Adoption was largely viewed as a voluntary process dependent upon the consent of a child's birth parents. Adoption and permanent care specialists were the only group to refer to the dispensation of parental consent as a means of obtaining an adoption order. Most decision makers understood that contact between children and their birth parents is possible following adoption, but this was not understood by all judicial officers or all child welfare specialists. Children's connection to their cultural heritage was viewed as important to the consideration of adoption for children in out-of-home care. This research provides insight into the foundations upon which decision makers may appraise adoption, within a hierarchy of options, as a potential outcome for children in need of permanency.